آثار الصلاة التربوية وبعض جوانبها الإعجازية: The Educational Impact of Prayer and Its Various Miraculous Aspects - MAHMOUD أماني الوليد محمود علي (الدراسات الإسلامية, 2023)
This paper investigates the multifaceted impacts of prayer (Ṣalāt) on personal development, transcending its mere ritualistic practice. Moving beyond the notion of prayer as a series of prescribed actions, it explores its profound influence on human life’s spiritual, physical, psychological, and social dimensions. Drawing upon Quranic verses and relevant hadith, the research analyses how prayer promotes individual character and fosters societal well-being. With particular emphasis on personal transformation, the paper argues that prayer serves as a cornerstone of Islamic self-cultivation. It examines how prayer shapes individual personality and promotes ethical conduct through its inherent elements of humility, discipline, and mindfulness. The analytical and narrative methodologies facilitate a nuanced understanding of prayer’s multifaceted effects, elucidating its role in Promoting a spiritual connection with Allah the Almighty, developing physical well-being through mindful movement and posture, enhancing psychological resilience through introspective practices, and educating social responsibility and community cohesion.